Hubungan Antara Disiplin Belajar dengan Hasil Belajar Statistika Dasar - Sumiyani Sumiyani (Jurnal Pendidikan Matematika:Judika Education, 2021)
This study aims to determine how big the relationship between learning discipline and basic statistics learning outcomes for students of Indonesian language and literature education in semester 1 of basic statistics course. The method used in this study is a descriptive method, which is a study that seeks to describe current problem solving based on existing data. The population and sample are students in the odd semester 2021/2022 class 5A.1. 5A.2 totaling 40 students. The results of the study, in general the student learning discipline went well. In general, student learning outcomes were categorized as good, as seen in the basic statistics learning outcomes obtained from daily test scores which had a value of 1550 with an average of 77.5. from the results of the calculation of t arithmetic of 3.785 and t table of 2.093, thus t arithmetic is greater than t table which means the hypothesis is accepted. In conclusion, there is a positive relationship between learning discipline and student learning outcomes in odd semesters of PBSI FKIP UMT Study Program Keywords: Learning Discipline, Learning Outcomes, Statistics